Gene and pathway analysis of genome-wide genetic associations of bladder cancer - Shi, Mingjun; Meng, Xiangyu; Xu, Xuan; Wang, Qiaoli ; 0000-0003-4152-7821 (Current Urology, 2025)
Background Although genetic variants associated with bladder cancer (BCa) risk have been identified through hypothesis-driven and genome-wide association studies, a systematic understanding of BCa genetic susceptibility at the gene and pathway levels remains to be achieved. Materials and methods In this 2-stage functional genomics study, we used 5 independent tools for genome-wide gene mapping and ranking based on BCa genome-wide association studies summary statistics, followed by a meta-analysis of gene-level significance p values, to obtain a consensus gene ranking in terms of association with BCa. Subsequently, we performed preranked gene-set enrichment analysis to identify the functional pathways involved in BCa genetic susceptibility. Joint analysis with gene-set enrichment analysis, based on somatic alteration frequency, was performed to explore the pathway-level relationships between genetic susceptibility and somatic alterations in BCa. Results Other than the well-known BCa genes (such as FGFR3, MYC, TERT, CCNE1, and TP63), we additionally prioritized a set of novel genes likely to be genetically implicated in BCa development, including SETD2, a possible tumor suppressor gene involved in chromatin remodeling. We further demonstrated convergence between genetic associations and somatic alterations at both the gene (eg, FGFR3 and TERT) and pathway levels (eg, cell cycle and chromatin modification), as well as functional ontologies specifically implicated in germline predisposition to BCa (eg, CD8/TCR signaling, immune checkpoints, and cytokine signaling). Conclusions We identified several novel genes associated with BCa and demonstrated that genetic variants contribute to the development of BCa by affecting antitumor immunity, response to toxic exposure, and RNA and protein homeostasis and synergizing with somatic alterations in various cancer-related pathways.
Publisher Copyright: © Wolters Kluwer Health, Inc. All rights reserved.
Keywords: Bladder cancer; Functional annotation; Genetic susceptibility; Genome-wide association studies; Pathway analysis